PERAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Lamria Sagala; Mitha Christina Ginting (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2021)
This research aims to analyze the role of financial performance as variable intervening factors that affect the value of companies in banking companies listed on the Indonesia Stock Exchange 2015-2019. The population in this study amounted to 34 companies using saturated sampling methods, so the sample in this study amounted to 34 samples. While the amount of data observed amounted to 170 analysis data (34 Companies X 5 Years). The data testing methods used are multiple linear regression analysis and path analysis. The results of the hypothesis study showed that partially, intellectual capital variables had positive significant effect on the value of the company, the quality of the application of good corporate governance had negative unsignificant effect on the value of the company, the capital structure had unsignificant effect on the value of the company. Financial performance is able to act as an intervening variable between intellectual capital variables and capital structure to the value of the company. Financial performance was unable to mediate the quality variables of the application of corporate governance to the value of the company in banking companies listed on the Indonesia Stock Exchange 2015-2019.